2016
DOI: 10.1093/cercor/bhv312
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Fluctuations in Visual Cortical Responses Influence Population Coding Accuracy

Abstract: Information processing in the cerebral cortex depends not only on the nature of incoming stimuli, but also on the state of neuronal networks at the time of stimulation. That is, the same stimulus will be processed differently depending on the neuronal context in which it is received. A major factor that could influence neuronal context is the background, or ongoing neuronal activity before stimulation. In visual cortex, ongoing activity is known to play a critical role in the development of local circuits, yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 105 publications
6
32
0
Order By: Relevance
“…However, pre-activation would likely correspond to a higher pre-stimulus response in regions that process a particular stimulus type, not lower as was seen here. Prior studies in early visual cortex in monkeys also showed that lower pre-stimulus activity is associated with 9 improved tuning and behavior (16,17,37). The results of the present study show that these faciliatory effects can be differentially focused in circuits associated with processing specific stimulus types in higher-level visual regions and in regions outside of visual cortex in humans.…”
supporting
confidence: 74%
“…However, pre-activation would likely correspond to a higher pre-stimulus response in regions that process a particular stimulus type, not lower as was seen here. Prior studies in early visual cortex in monkeys also showed that lower pre-stimulus activity is associated with 9 improved tuning and behavior (16,17,37). The results of the present study show that these faciliatory effects can be differentially focused in circuits associated with processing specific stimulus types in higher-level visual regions and in regions outside of visual cortex in humans.…”
supporting
confidence: 74%
“…On the one hand, spontaneous depolarization brings neurons closer to threshold prior to the arrival of excitatory sensory input. Accordingly, some studies show that enhanced levels of prestimulus activity correspond to larger responses 46,[48][49][50] . On the other hand, spontaneous synaptic barrages reduce input resistance 19,51,52 and depress synapses [53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…Individual pattern probabilities during SA (grey screen) and nat movies appeared to be fairly similar, both visually and in terms of the JSD, whilst mG seemed to modulate pattern probabilities differently. The experimental design allowed for comparing SA recorded at different times during the experiment, which enabled us to account for different brain states or network excitability levels 5,8,13 . Particularly nat movies and S2 recorded in close temporal coherence (interleaved between stimulus repetitions) revealed a low divergence of pattern distributions with values comparable to divergences between SA recorded at early and late experimental phases.…”
Section: /16mentioning
confidence: 99%
“…In addition, it has been suggested 30, 32 that instead of pairwise correlations between spike trains, population FR fluctuations may be responsible for the different pattern distributions and that considering population rate dynamics over simply mean FR was required to account for FR statistics 36 and that fluctuations in ongoing activity play an important role in population FR 13 . There has been considerable research into this with different models 13,24,30,36,37 . Population dynamics, and population FR differences between the various stimulus regimes could be implicated in the observed divergences.…”
Section: /16mentioning
confidence: 99%
See 1 more Smart Citation